2009
DOI: 10.2109/jcersj2.117.302
|View full text |Cite
|
Sign up to set email alerts
|

Advanced colloidal techniques for characterization of the effect of electrosteric dispersant on the colloidal stability of nanocrystalline ZrO2 suspension

Abstract: The adsorption state and dispersion effect of an anionic polyelectrolyte (Dolapix CE64) dispersant on the stability of nanocrystalline ZrO2 suspensions are studied by using adsorption isotherms, sedimentation, TGA, electrokinetic sonic amplitude (ESA) and Auger electron spectroscopy (AES) techniques. It was found that colloidal stability and surface properties of aqueous ZrO2 suspension are closely related to coverage distribution of polyelectrolyte as a function of pH on nanocrystalline ZrO2 particle surface.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…The calculation of the ζ-potential from the dynamic mobility has to consider the size, density and frequency dependent inertia forces. O'Brien 7) has formulated a Smoluchowski type formula relating the high frequency or dynamic mobility to the particle zeta potential: (2) ε dielectric permittivity of the suspension ζ zeta potential η viscosity f factor considering the diameter relation of particle and double layer G(α) considers the inertia forces of the particles at high frequency The equation for converting the ESA amplitude to the (ζ) zetapotential becomes:…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The calculation of the ζ-potential from the dynamic mobility has to consider the size, density and frequency dependent inertia forces. O'Brien 7) has formulated a Smoluchowski type formula relating the high frequency or dynamic mobility to the particle zeta potential: (2) ε dielectric permittivity of the suspension ζ zeta potential η viscosity f factor considering the diameter relation of particle and double layer G(α) considers the inertia forces of the particles at high frequency The equation for converting the ESA amplitude to the (ζ) zetapotential becomes:…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Of the different water-soluble anionic polyelectrolyte dispersants available (e.g., PAA, PMAA), a new type of commercially available electrosteric dispersant agent, Dolapix CE64 (Zschimmer & Schwartz GmbH Co., Germany) was found to be the most suitable choice on basis of physical and chemical properties as well as practical experiments reported by different authors [3,[42][43][44][45][46][47][48][49][50][51][52]. According to the manufacturer information and result reported by different authors, Dolapix CE64 contains aqueous solution (~ 70 mass%) and ammonium salt (~ 30 mass%) of poly-(methacrylic acid) (PMAA-NH 4) , with a pH of 9 [3,[43][44][45][46][47][48][49][50][51][52].It has a molecular weight of 660 g/mol with a density (20°C) of approximately 1.2 g/cm 3 [3,[43][44][45][46][47][48][49][50][51][52]. It can easily dissociate in water and produces negatively charged polyions and ammonium counter-ions that create stability based on electrosteric interactions [3,[43][44][45][46][47][48][49]…”
Section: Dispersant Characterizationmentioning
confidence: 99%
“…The dispersion of the suspensions using Dolapix CE64 is driven by an electrosteric mechanism [16]. The carbonic acid-based polyelectrolyte chains interact with the charged surface of the particles, causing the formation of a thin organic layer on the particles which prevent the attractive van-der-Waals forces between particles, and thus flocculation is avoided [3,16,19]. However, our results have shown that this mechanism is limited, since it was not possible to synthesize slurries containing more than 60 wt% of solids content (TH).…”
Section: Evaluation Granulates After the Brazing Processmentioning
confidence: 99%
“…The presence of organic molecules on the particles caused tightening of the outer shell preventing the remaining water Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 6/19/15 2:33 AM from evaporating and increasing the pressure inside the granules. Since the temperature during the spray drying process (between T in = 230°C and T out = 102°C) was not high enough to cause pyrolysis of the additive Dolapix CE64, which is reported to occur at temperatures between 230 and 490°C [19], granulate defects such as doughnut structure, hollow structure, or fracture of the spheres occurred [14]. The other applied organic deflocculant, trisodium citrate, did not show this effect since its pyrolysis temperature of approximately 150°C (manufacturer data) was surpassed.…”
Section: Evaluation Granulates After the Brazing Processmentioning
confidence: 99%